Aerobic Denitrification Reactor with Pseudomonas chloritidismutans K14 Improves Water Quality and Growth of Hybrid Grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) in RAS - Xueliang Sun; Yan Zhuang; Yue Sun; Xiaohan Yang; Yunchen Tian; Hongyue Shi; Zhenzhen Fang; Shuwang Hou; Hong Yu; Xiaoya Yin (Fishes, 2026)
The intensification of mariculture has increased nitrogen and phosphorus pollution in aquaculture wastewater. Conventional treatments often prove inefficient under saline conditions. To address this challenge, we developed an innovative aerobic denitrification reactor using Pseudomonas chloritidismutans K14, specifically tailored for seawater systems. Our study examined the effects of hydraulic retention time (HRT) and carbon-to-nitrogen (C/N) ratio on pollutant removal and critically assessed the physiological benefits for hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂). At an optimal HRT of 8 h and a C/N ratio of 8, the system achieved high removal efficiencies: 95.5% for NH4+-N, 92.4% for NO2−-N, 93.8% for NO3−-N, 92.8% for total nitrogen (TN), and 84.8% for chemical oxygen demand (COD), along with a 47.3% reduction in total phosphorus (TP). More importantly, the system significantly enhanced grouper health by improving growth performance, digestive enzyme activities, and antioxidant capacity, along with a trend toward improved nonspecific immune indicators. The feed conversion ratio was optimized to 2.28, with a weight gain rate of 117.07%. Our findings establish this optimized aerobic denitrification system as an integrated strategy that effectively combines water purification with indirect health benefits, offering a sustainable solution for mariculture.